Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

Phosphorus species transformation and recovery in deep eutectic solvent-assisted hydrothermal carbonization of sewage sludge - Rui Dou; Fan Gao; Yi Tan; Huan-Ran Xiong; Zhi-Xiang Xu; Sameh M. Osman; Li-Jun Zheng; Rafael Luque (Sustainable Chemistry and Pharmacy, 2024)

Hydrochar-based facile and greenwood bio-adhesives production from distilled spent grain - Zhi-Xiang Xu; Huan-Ran Xiong; Rui Dou; Yi Tan; Yong-Xing Chen; Li-Jian Leng (Chemical Engineering Journal, 2024)

Integration of deep learning algorithms with a Bayesian method for improved characterization of tropical deforestation frontiers using Sentinel-1 SAR imagery - Rui Sun; Feng Zhao; Chengquan Huang; Huabing Huang; Zhong Lu; Ping Zhao; Xiang Ni; Ran Meng (Remote Sensing of Environment, 2023)

The first homosporous lycophyte genome revealed the association between the recent dynamic accumulation of LTR-RTs and genome size variation - Ji-Gao Yu; Jun-Yong Tang; Ran Wei; Mei-Fang Lan; Rui-Chen Xiang; Xian-Chun Zhang; Qiao-Ping Xiang (Plant Molecular Biology, 2023)

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

Anti-bacterial effects of components from Sanguisorba officinalis L. on Vibrio vulnificus and their soluble epoxide hydrolase inhibitory activity - Xiang Dong Su; Rui Hong Guo; Seo Young Yang; Young Ho Kim; Young Ran Kim (Natural Product Research, 2019)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .